PD-L1-Binding Antigen Presenters: Redirecting Vaccine-Induced Antibodies for Tumor-Agnostic Immunotherapy - Gao, Huixin; Lu, Lijuan; Xiong, Xiaoxiao; Li, Yi; Hu, Donghui; Zhang, Duo; Feng, Zhiwei; Liu, Cong; Liu, Nannan; Li, Xiaoli; Tan, Jizhou; Liu, Ting; et al. (浪淘沙预印本平台, 2026)
The efficacy of immunotherapy in enhancing antitumor immunity in solid tumors remains limited, primarily due to the insufficient immunogenicity of tumor cells. In contrast, vaccination and natural viral infections can generate durable, high-titer antiviral antibodies. A modular Programmed Death-Ligand 1 (PD-L1)-binding antigen presenter (PBAP-gE) has been engineered to tether varicella-zoster virus glycoprotein E (gE) to PD-L1 expressed on tumor cell surfaces. This innovative construct leverages pre-existing anti-gE antibodies to trigger antibody-dependent effector mechanisms. PBAP-gE effectively bound to PD-L1-positive tumor cells and, together with vaccine-induced anti-gE antibodies, potentiated NK cell-mediated antibody-dependent cellular cytotoxicity (ADCC) in vitro and induced significant tumor regression in murine models. The PBAP platform is modular and versatile. For example, a PBAP-Her2 construct synergized with Trastuzumab and Kadcyla to kill Human Epidermal growth factor Receptor 2 (HER2)-negative, PD-L1-positive cells. This strategy represents an innovative strategy for enhancing PD-L1-targeted therapies by leveraging pre-existing antibodies induced by viral infections or vaccines, alongside commercially available antibody-based therapies.